2011
DOI: 10.1111/j.1469-1809.2011.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Subtelomeric Deletion of the Long Arm of Chromosome 6

Abstract: SummaryPure subtelomeric deletion of the long arm of chromosome 6 is rare. The frequency of this deletion accounts for approximately 0.05% of subjects with intellectual disability and developmental delay with or without dysmorphic features. Common phenotypes associated with this deletion include intellectual disability, developmental delay, dysmorphic features, seizure, hypotonia, microcephaly and hypoplasia of the corpus callosum. The smallest overlapped region is approximately 0.4 Mb, and contains three know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 71 publications
(88 reference statements)
0
26
1
Order By: Relevance
“…Pure terminal deletions of the long arm of chromosome 6 are rare chromosomal abnormalities and present with variable clinical features. The frequency of this deletion accounts for approximately 0.05% of subjects with intellectual disability, developmental delay, hypotonia, seizure, and multiple malformations (Eash et al, ; Bertini et al, ; Rooms et al, ; Striano et al, ; Lee et al, ). Similar clinical features have been described in unrelated patients with variable deletion sizes including the case reported here, suggesting that genes responsible for the phenotypic features of 6q deletions reside in the distal 6q27 region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure terminal deletions of the long arm of chromosome 6 are rare chromosomal abnormalities and present with variable clinical features. The frequency of this deletion accounts for approximately 0.05% of subjects with intellectual disability, developmental delay, hypotonia, seizure, and multiple malformations (Eash et al, ; Bertini et al, ; Rooms et al, ; Striano et al, ; Lee et al, ). Similar clinical features have been described in unrelated patients with variable deletion sizes including the case reported here, suggesting that genes responsible for the phenotypic features of 6q deletions reside in the distal 6q27 region.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal deletions of the long arm of chromosome 6 are rare chromosomal abnormalities. The common postnatal phenotypes associated to 6q subtelomeric deletion include developmental delay, congenital hydrocephalus, seizures, hypotonia, microcephaly, and hypoplasia of the corpus callosum (Anderlid et al, ; Eash et al, ; Lee et al, ). Most of the reported cases are sporadic although a few families with multiple affected family members have been described (Le Caignec et al, ; Adeyinka et al, ; Rooms et al, ; Auber et al, ; Wadt et al, ; Conti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the proband exhibited features that are known to be associated with the terminal 6q deletion phenotype. This fetus presented bilateral hydrocephalus/ventriculomegaly and a lumbar hemivertebrae but lacked the typical phenotypic features of subtelomeric 6q deletion, such as developmental delay, corpus callosum anomalies, microcephaly, cleft palate and hyperactivity [ 2 , 3 , 5 ], which was considered unusual for such a large deletion, spanning 10.04 Mb. Until now, very few cases of prenatal ventriculomegaly due to submicroscopic terminal 6q deletions have been reported, and in those cases, the extent of the deletion with respect to non syndromic ventriculomegaly was less than 5 Mb [ 5 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated 6q subtelomeric deletions are relatively rare, and few correlative studies have been reported [ 1 4 ]. The most common clinical features include mental retardation, developmental delay, dysmorphic features, hypotonia, microcephaly, facial dysmorphism, seizures, cardiac defects and brain anomalies, such as abnormal corpus callosum and hydrocephalus [ 1 , 3 , 5 ]. Patients with pure 6q terminal deletions usually present multiple anomalies and seldom present less than three malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fragile FRA6E site located in 6q26 extends over 3.6 Mb and contains eight genes: IGF2R , SLC22A1 , 2 and 3 , PLG , LPA , MAP3K4 and PARK2 [Denison et al, ; Palumbo et al, ]. Bertini et al [] and Lee et al [] have suggested that a breakage in FRA6E may lie at the origin of 6q deletions. Thus, this fragile site could play the role of acceptor‐site for the insertion of dup 2.…”
Section: Discussionmentioning
confidence: 99%